Endogenous and maximal sarcoplasmic reticulum calcium content and calsequestrin expression in type I and type II human skeletal muscle fibres - C. R. Lamboley; Robyn M. Murphy; Michael J. McKenna; Graham D. Lamb (2013)
Ca2+ release from the sarcoplasmic reticulum (SR) controls contraction in vertebrate skeletal muscle. Calsequestrin (CSQ) is thought to be the principal Ca2+ binding protein in the SR but little is known about SR Ca2+ content and loading characteristics, or CSQ isoform distribution, in human skeletal muscle fibres. Type I (slow-twitch) and type II (fast-twitch) skeletal muscle fibres in young healthy adults show highly-stereotyped patterns of isoform expression of CSQ and SR Ca2+ pumps, in tight correspondence with isoform expression of the contractile proteins, which probably facilitates optimal contractile function in the individual fibre types. Endogenous Ca2+ content of the SR is slightly larger in type II fibres than in type I fibres, but its maximal capacity is substantially greater, probably due to the larger amount of the CSQ1 isoform present. SR Ca2+ content and capacity in type I fibres is probably determined by their content of both CSQ1 and CSQ2. Abstract The relationship between sarcoplasmic reticulum (SR) Ca2+ content and calsequestrin (CSQ) isoforms was investigated in human skeletal muscle. A fibre-lysing assay was used to quantify the endogenous Ca2+ content and maximal Ca2+ capacity of the SR in skinned segments of type I and type II fibres from vastus lateralis muscles of young healthy adults. Western blotting of individual fibres showed the great majority contained either all fast or all slow isoforms of myosin heavy chain (MHC), troponins C and I, tropomyosin and SERCA, and that the strontium sensitivity of the force response was closely indicative of the troponin C isoform present. The endogenous SR Ca2+ content was slightly lower in type I compared to type II fibres (0.76 ± 0.03 and 0.85 ± 0.02 mmol Ca2+ per litre of fibre, respectively), with virtually all of this Ca2+ evidently being in the SR, as it could be rapidly released with a caffeine-low [Mg2+] solution (only 0.08 ± 0.01 and <0.07 mmol l−1, respectively, remaining). The maximal Ca2+ content that could be reached with SR Ca2+ loading was 1.45 ± 0.04 and 1.79 ± 0.03 mmol l−1 in type I and type II fibres, respectively (P < 0.05). In non-lysed skinned fibres, where the SR remained functional, repeated cycles of caffeine-induced Ca2+ release and subsequent Ca2+ reloading similarly indicated that (i) maximal SR Ca2+ content was lower in type I fibres than in type II fibres (P < 0.05), and (ii) the endogenous Ca2+ content represented a greater percentage of maximal content in type I fibres compared to type II fibres (∼59% and 41%, respectively, P < 0.05). Type II fibres were found on average to contain ∼3–fold more CSQ1 and ∼5–fold less CSQ2 than type I fibres (P < 0.001). The findings are consistent with the SR Ca2+ content characteristics in human type II fibres being primarily determined by the CSQ1 abundance, and in type I fibres by the combined amounts of both CSQ1 and CSQ2. Contraction of mammalian skeletal muscle is regulated by the intracellular Ca2+ level (Ebashi et al. 1969; Gordon et al. 2000). In the resting state, most cellular Ca2+ is stored within the sarcoplasmic reticulum (SR; Somlyo et al. 1981; Berchtold et al. 2000), bound in large part to high-capacity, low-affinity Ca2+-binding proteins, in particular calsequestrin (CSQ; MacLennan & Wong, 1971; Beard et al. 2004; Park et al. 2004; Rossi & Dirksen, 2006; Murphy et al. 2009a). Two isoforms of calsequestrin are found in mammalian skeletal muscle, calsequestrin–1 (CSQ1) and calsequestrin–2 (CSQ2); in rabbit, rat and mouse, type II fibres contain predominantly or exclusively the CSQ1 isoform, and type I fibres contain appreciable amounts of both CSQ1 and CSQ2 (Damiani et al. 1990; Paolini et al. 2007; Murphy et al. 2009a). The absolute Ca2+ content of individual fibres from rat skeletal muscle has been measured for different SR load states, using a fibre-lysing technique (Fryer & Stephenson, 1996; Owen et al. 1997). When the SR of the skinned fibres was loaded at close to its normal endogenous state, the total fibre Ca2+ content was ∼1.3 mmol per litre fibre volume both in type I fibres from soleus muscle and type II fibres from extensor digitorum longus (EDL) muscle, of which all but ∼0.25 mmol l−1 could be released by exposing the skinned fibre to a caffeine-low Mg2+ release solution or by repeated depolarizations (Fryer & Stephenson, 1996; Owen et al. 1997). The maximal Ca2+ content level reached following maximal loading of the SR, however, was found to be far lower in the type I fibres (∼1.35 mmol l−1) than in the type II fibres (∼3.9 mmol l−1). It was subsequently shown that the maximal Ca2+ content levels in the two fibre types could each be accounted for by the absolute amounts of CSQ1 and CSQ2 present, ∼10 μmol l−1 CSQ1 and ∼5 μmol l−1 CSQ2 in soleus type I fibres and ∼36 μmol l−1 CSQ1 in EDL type II fibres (Murphy et al. 2009a). Little is known, however, about the SR Ca2+ content and loading characteristics, or the CSQ isoform distribution, in human skeletal muscle fibres. The endogenous Ca2+ content in mixed fibre samples of vastus lateralis muscle of young adults was found by atomic absorption to be ∼0.7 mmol per litre fibre volume (Overgaard et al. 2004). Another study using chemically skinned fibres (of unspecified type) from human pectoralis muscle found that the total Ca2+ content reached after maximally loading the SR was only ∼0.8 mmol l−1 (Salviati et al. 1982), very much lower than seen in rat fibres. It remains unknown whether the endogenous SR Ca2+ content and maximal SR Ca2+ capacity differ between type I and type II fibres in human muscle, and how such Ca2+ content values relate to the CSQ isoforms present. Here we use the fibre-lysing assay utilised previously with rat muscle fibres (Fryer & Stephenson, 1996; Owen et al. 1997) to measure the amount of Ca2+ present in individual type I and type II fibres from vastus lateralis muscle of young healthy human subjects. We assess not only the endogenous Ca2+ content but also the Ca2+ content present after maximally loading or fully depleting the SR. Further, we use western blotting to measure the relative amounts of CSQ1 and CSQ2 present in the fibres, as well as the isoform expression of sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA), the SR Ca2+ pump, and also myosin heavy chain (MHC) and other key contractile proteins. It was hypothesized that (i) individual fibres from these young adult subjects would have highly stereotyped, fibre-specific isoform distribution patterns of both the SR and contractile proteins, because close coordination of SR and contractile properties would help optimize contractile function in each fibre type, (ii) there would be less disparity in the SR Ca2+ content characteristics between type I and type II fibres in humans compared to rat, as human muscle lacks the very fast type IIB fibres present in rat muscle, and (iii) the SR Ca2+ content characteristics of the human fibres would be explicable in terms of the relative amounts of the particular CSQ isoforms present. All protocols and procedures were approved by the Human Research Ethics Committees at Victoria University and La Trobe University. Informed consent was obtained in writing from all subjects and the studies conformed to the standards set by the Declaration of Helsinki. All the experiments on human skinned fibres were performed on fibres obtained from vastus lateralis muscle biopsies from 23 rested subjects, comprising sixteen males and seven females (age 24 ± 5 years; height, 173 ± 10 cm; body mass, 70 ± 11 kg; mean ± SD). All subjects were healthy and most participated in regular physical activity but were not specifically trained in any sport. After injection of a local anaesthetic (1% lidocaine (lignocaine)) into the skin and fascia, a small incision was made in the middle third of the vastus lateralis muscle of each subject and a muscle sample taken using a Bergstrom biopsy needle (McKenna et al. 2006). An experienced medical practitioner took all biopsies at approximately constant depth. The excised muscle sample was rapidly blotted on filter paper to remove excess blood and placed in paraffin oil (Ajax Chemicals, Sydney, Australia) at 10°C for 45 min before individual muscle fibres were dissected. The remaining muscle sample from the biopsies was frozen and stored in liquid nitrogen for later analyses. The muscle biopsy was pinned at resting length in a Petri dish containing paraffin oil (Ajax Chemicals, Sydney, Australia), and kept cool (∼10°C) on an icepack. As described previously (Murphy et al. 2009b; Dutka et al. 2012), individual fibre segments were mechanically skinned and mounted at 120% of resting length on a force transducer (AME801, SensoNor, Horten, Norway), and then placed in a Perspex bath containing 2 ml of the standard K+-based solution broadly mimicking the intracellular milieu (see below). Force responses were recorded using a Bioamp pod and Powerlab 4/20 series hardware (ADInstruments, Sydney, Australia). All experiments were performed at room temperature (∼23 ± 2°C). All chemicals were purchased from Sigma-Aldrich (St Louis, MO, USA) unless specified otherwise. The standard K-HDTA solution contained (in mm): hexa-methylene-diamine-tetraacetate (HDTA2−), 50 (Fluka, Buchs, Switzerland); total ATP, 8; Na+, 36; K+, 126; total Mg2+, 8.5 (giving 1 mm free [Mg2+]); creatine phosphate, 10; total EGTA, 0.05; Hepes, 90; pH 7.1 and pCa (−log10[Ca2+]) ∼7.2, except where stated. Free [Ca2+] for pCa < 7.3 was determined with a Ca2+-sensitive electrode (Orion Research, Boston, MA, USA). Where required, the SR of the skinned fibre was totally depleted of all releasable Ca2+ by exposure to the 'full release solution', which was similar to the K-HDTA solution but with 30 mm caffeine, 0.05 mm free Mg2+ (total Mg2+ of 2.1 mm) and 0.5 mm free EGTA (pCa 8.5) present to chelate released Ca2+. Where required, the SR was reloaded with Ca2+ by exposing the fibre for a set period (from 15 s to 3 min) to the load solution, which was the same as the standard K-HDTA solution but with the pCa buffered at 6.7 with 1 mm total CaEGTA–EGTA. Under these conditions, a 3 min load period was sufficient to load the SR to close to its maximum capacity. When examining the properties of the contractile apparatus, it was necessary to use heavily Ca2+-buffered solutions in which all HDTA was replaced with EGTA (relaxing solution) or CaEGTA (maximum Ca2+-activating solution), as described previously (Lamb & Posterino, 2003). The relaxing solution had no added Ca2+ (pCa > 9) and the maximum Ca2+-activating solution ('max') had 49.5 mmol l−1 added Ca2+ (pCa 4.7), with total Mg2+ of 10.3 and 8.1 mm, respectively, to maintain the free [Mg2+] at 1 mm. These two solutions were mixed in appropriate ratios to produce solutions with pCa in the range 6.7–4.7. In addition, a strontium-based solution (at pSr 5.2) was made by mixing relaxing solution (50 mm EGTA) with Sr-EGTA solution similar to the maximum Ca2+-activating solution. The solution used to pre-equilibrate fibres before lysing was similar to the standard K-HDTA solution but had no EGTA and instead had 0.025–1.8 mm BAPTA, added from a 47 mm BAPTA stock solution. The BAPTA stock solution was titrated with Ca2+ using a Ca2+-sensitive electrode (Orion Research, Boston, MA, USA) to establish the exact amount of BAPTA present. In some experiments 50 μm 2,5-di-tert-butyl-1,4-hydroquinone (TBQ) was present in both the full release solution and BAPTA pre-equilibration solution to block Ca2+ binding to SERCA pumps. TBQ was added from a freshly prepared 50 mm stock solution in DMSO. The total amount of Ca2+ contained in a fibre after a given treatment can be quantified by pre-equilibrating the skinned fibre in a solution with a known concentration of the very fast calcium buffer BAPTA and then transferring the fibre to an emulsion of 10% Triton X-100 and paraffin oil (TX–oil) to lyse all membranous compartments and release any Ca2+ from within the fibre. This procedure has been described comprehensively elsewhere (Fryer & Stephenson, 1996; Owen et al. 1997). Briefly, the skinned fibre was first placed in the standard solution K-HDTA for 2 min to wash out all the diffusible Ca2+-binding proteins present endogenously in the cytoplasm. Then the fibre was pre-equilibrated for 20 s in a solution with a particular [BAPTA] before placing the fibre in a freshly triturated emulsion of Triton X-100 in paraffin oil (TX–oil) (10% v/v). The paraffin oil formed a closed compartment around the skinned fibre and the detergent lysed all intracellular membranes and liberated Ca2+ from intracellular stores. As a result, the released Ca2+ rapidly binds to the known amount of BAPTA within the fibre and to other sites, predominantly troponin C (TnC). If the pre-equilibrating [BAPTA] was chosen such that the fibre produced a finite, non-maximal force response upon lysis, then the total amount of Ca2+ present in the fibre could be calculated in absolute terms from the [BAPTA] in the equilibration solution and the magnitude of the force response (see 'Calculation of Ca2+ release from lysing experiment'). To check that the peak force upon lysis had not reached maximum, the fibre was washed in relaxing solution and then activated in the maximum Ca2+-activation solution. Finally, the fibre was moved back into the TX–oil emulsion again to determine whether the maximum force produced was the same in the TX–oil environment as in free solution. Other skinned fibre segments, prior to the TX–oil lysing, were (i) fully depleted of their endogenous SR Ca2+ content by a 1 min exposure to the full release solution, or (ii) loaded to their maximal SR Ca2+ capacity by a 4 min exposure to standard load solution (pCa 6.7, buffered with 1 mm total EGTA; see 'Skinned fibre solutions'). The total Ca2+ content within the fibre at the time of lysis ([Ca2+]T), expressed in millimoles per litre total fibre volume (in keeping with previous studies: Fryer & Stephenson, 1996; Owen et al. 1997), could be calculated as the sum of (i) the Ca2+ bound to BAPTA, (ii) the Ca2+ bound to all other high affinity binding sites in the fibre (predominantly TnC), and (iii) the free Ca2+ in the myoplasm ([Ca2+]). As mentioned, prior to lysis all skinned fibres were bathed for 2 min in the standard K-HDTA solution to ensure all diffusible Ca2+ buffers had been washed out and would not affect the Ca2+ content estimate. Furthermore, this K-HDTA solution had very little contaminating Ca2+ and very weak Ca2+ buffering (0.05 mm total EGTA, pCa ∼7.2), so that the SR could not take up any substantial net amount of Ca2+ from the bathing solution but nevertheless could still readily recover most or all of any Ca2+ that leaked from the SR into the cytoplasmic space within the fibre. The total amount of Ca2+ within the fibre after various treatments was calculated as follows. The cytoplasmic free Ca2+ concentration ([Ca2+], in molar units) prevailing in the fibre during the finite force response upon lysis was derived from the mean Hill curve describing the relationship between force and [Ca2+]: The effective [BAPTA] within the fibre (in mM) was taken as being 1.13 times the [BAPTA] of the pre-equilibration solution, to account for the swelling of the fibre when initially placed in solution, and also the fibre volume to which BAPTA is not accessible (i.e. that occupied by the SR, t-tubular system, and mitochondria etc. (Eisenberg, 1983; Owen et al. 1997). The percentage of BAPTA with bound Ca2+ (%CaBAPTA) was determined from the percentage force, F, as follows: The total possible increase in Ca2+ binding to TnC was taken here as 70 and 140 μmol l−1 binding to the Ca2+-specific sites in type I and type II fibres, respectively, and a further 140 μmol l−1 binding to the non-Ca2+-specific sites present in both (i.e. 1 or 2 Ca2+-specific sites and 2 non-specific sites per TnC molecule; Fryer & Stephenson, 1996). For experiments where a fibre was pre-equilibrated in [BAPTA] > 0.5 mm (and hence pCa > 8.3), the amount of Ca2+ binding to TnC (CaTnC) (in mmol l−1) as a function of force was calculated from the data of Fuchs (1985) and Robertson et al. (1981) as being: Ca2+ binds to the ATP and HDTA present, and the total of these and the free [Ca2+] was estimated as being ∼9.6 ×[Ca2+] (Posterino & Lamb, 2003). Finally, 0.015 mmol l−1 was deducted from the total to take into account the contaminating Ca2+ present in the BAPTA pre-equilibration solution. As the muscle fibres were kept and skinned under paraffin oil, the SR initially retained its endogenous level of Ca2+. The procedure to assess the relative endogenous and maximal SR Ca2+ content has been described comprehensively elsewhere (Trinh & Lamb, 2006). Briefly, each skinned fibre segment was first bathed for 2 min in the standard K-HDTA solution to wash out all diffusible Ca2+ buffers present endogenously in the cytoplasm. The SR was then depleted of all of its releasable Ca2+ by exposing the fibre to the full release solution (see above). The fibre was then washed for 1 min in standard K-HDTA solution (with 0.5 mm free EGTA present to prevent any Ca2+ reuptake), and subjected to repeated load–release cycles as follows. Step 1: Load SR for a set time (15–180 s) in standard load solution (pCa 6.7 with 1 mm total CaEGTA–EGTA). Step 2: Pre-equilibrate skinned fibre for 15 s in K-HDTA solution with 0.5 mm free EGTA. Step 3: Empty SR of all releasable Ca2+ by exposing fibre for 60 s to full release solution. Step 4: Wash skinned fibre for 1 min in K-HDTA solution with 0.5 mm free EGTA. The time integral (area) of the force response to the initial exposure to the full release solution was indicative of the endogenous SR Ca2+ content initially present in the fibre, and the responses to the subsequent exposures indicated the SR content for the respective load time (e.g. see Fig. 4). The relationship between the time integral of the force response and load time was well fitted by an exponential fit approaching saturation after ∼180 s (Fig. 4C). The parameters were adjusted (Fig. 4D) to take into account (1) the true maximum SR Ca2+ content, derived by extrapolation of the exponential fit to longer load times, and (2) the amount of SR Ca2+ that had to be released to elicit any detectable force in the presence of 0.5 mm EGTA, determined by back-extrapolation of the response area–load time curve to zero load time (Fig. 4C; see Murphy et al. 2009a). The force–Ca2+ relationship in type I and type II fibres was determined by exposing skinned fibre segments to a sequence of heavily buffered solutions at progressively higher free [Ca2+] (50 mm CaEGTA–EGTA, pCa > 9–4.7, the latter value eliciting maximum force). Isometric force responses produced at each [Ca2+] were expressed as a percentage of the corresponding maximum force and analysed by fitting a Hill curve using GraphPad Prism 4 software to ascertain the pCa50 (pCa at half-maximum force) and Hill coefficient (h) for each sequence. Individual skinned fibre segments were placed in a small volume (10 μl) of 1x solubilizing buffer which contained 0.125 m Tris-HCl, 10% glycerol, 4% SDS, 4 m urea, 10% mercaptoethanol and ∼0.001% bromophenol blue (pH 6.8) diluted (2:1 v/v) with double distilled water. Fibres were stored at −80°C until analysed by western blotting. Total protein in the single fibres was separated on 4–15% Criterion Stain Free gels (Bio-Rad, Hercules, CA, USA), as previously described (Murphy, 2011). After appropriate washes and blocking, membranes were probed with the required primary antibody (see Table 1), being constantly rocked overnight at 4°C and for 2 h at room temperature (RT) and then incubated with the appropriate secondary antibody (2 h, RT). Chemiluminescent images were captured and densitometry performed using Chemidoc MP and ImageLab software (BioRad). For each fibre the density of the myosin heavy chain (MHC) band on the Stain Free gel was used as the measure of the relative amount of protein loaded. The densities of the CSQ bands in a given fibre were expressed relative to the MHC density for that fibre, and the resulting values then normalized to the mean obtained in all type I fibres (CSQ2) or in all type II fibres (CSQ1) run on that same gel, enabling subsequent amalgamation of data from different gels (Fig. 6). Fibre type was defined by the predominant MHC isoform present (e.g. Fig. 1B and related text), as detected with antibodies to MHC I or MHC II (Table 1). Every fibre in the present study was positive to MHC I or MHC II or both. Contractile properties and isoform expression in human skeletal muscle fibres A, representative force–Ca2+ relationships in a type I (•) and a type II (▴) fibre from a vastus lateralis muscle biopsy from a young, healthy adult. pCa =−log10[Ca2+]. The best-fit Hill curves had pCa50 (pCa at half-maximum force) and h coefficient, respectively, of 5.96 and 4.4 for the type I fibre, and 5.84 and 5.3 for the type II fibre. B, western blotting of multiple proteins in a single fibre segment; representative examples shown of a type I fibre, a type II fibre, and a 'mixed' fibre, the latter being very uncommon in young, healthy adults (5 out of 153 fibres analysed). Type I fibres contained almost exclusively only 'slow' isoforms of contractile apparatus proteins (MHC, TnI, TnC) and SERCA pumps, type II fibres only 'fast' isoforms, and mixed fibres contained both slow and fast isoforms. MHC band density in Stain Free image (top) indicates relative amount of tissue loaded in given lane. Values are presented individually, or as mean ± SEM or mean ± SD as indicated, with n denoting the number of fibres examined and N the number of subjects. Statistical significance (P < 0.05) was determined with Student's t test or the non-parametric Mann–Whitney rank test as appropriate. The Ca2+ sensitivity of the contractile apparatus in human skinned muscle fibre segments was determined by directly activating the contractile apparatus in solutions with free [Ca2+] strongly buffered in the range pCa 6.7–4.7 (see Methods), and fitting the resulting force–pCa data with a Hill curve (e.g. Fig. 1A). In addition, the force response to a strontium-based solution at pSr 5.2 was also determined in each fibre (e.g. Fig. 2A). After completing all relevant force measurements, including any assessment of SR Ca2+ content and loading (see below), the fibre segment was placed in SDS and western blotting subsequently employed to determine the isoform profile and relative amounts of a range of contractile and SR proteins (e.g. Fig. 1B). In the great majority of fibres examined from the young healthy subjects (>95% of 153 fibres), the myosin heavy chain (MHC) isoform present was almost entirely either MHC I or MHC II, such fibres being defined as 'type I' and 'type II' respectively. The small number of remaining fibres contained appreciable amounts of both MHC I and MHC II, and were denoted as being 'mixed' fibres (e.g. Fig. 1B). In virtually every case, the type I fibres contained only the slow isoforms of TnC and TnI, the type II fibres contained only the fast isoforms, and the mixed fibres contained both the slow and fast isoforms of both troponins. A similar tight relationship between fibre type (i.e. MHC isoform) and TnC isoform has been reported in rat skeletal muscle (O'Connell et al. 2004). It was further found here that the human type II fibres containing solely the fast TnC isoform were much less sensitive to activation by Sr2+ than were the type I fibres containing solely the slow TnC isoform. In every case, type II fibres gave little or no force to a solution at pSr of 5.2 (<5% of maximum force), type I fibres gave >80% of maximum force (e.g. Figs 2A and 4), and mixed fibres gave an intermediate force response (10–70%), all in close accord with the Sr2+ responses found previously in rat fibres (Bortolotto et al. 2000). Ca2+ content assay in human type II fibre segments in three different SR load states A, a skinned fibre segment with endogenous Ca2+ content was briefly equilibrated with 0.7 mm free BAPTA and when lysed in the Triton–paraffin oil emulsion (TX–Oil) produced ∼40% of maximal force. Fibre subsequently activated in aqueous solutions buffered at various pCa and each time again transferred to TX–oil to gauge its effect. Fibres washed in relaxing solution between solution changes. Fibre gave very little force to a Sr2+ solution at pSr 5.2. B, a skinned fibre segment in which the SR was maximally loaded (by 4 min in pCa 6.7 load solution) required equilibration with 1.6 mm BAPTA in order to yield a similar size force response when lysed in TX–oil. C, a skinned fibre segment that had been emptied of SR Ca2+ (by exposure to caffeine-low [Mg2+] solution) and then equilibrated in 0.025 mm BAPTA produced only a small force response upon lysis in TX–oil. Western blotting subsequently showed all segments were from type II fibres. In the 40 type I fibres (from 12 subjects) in which the force–pCa relationship was determined, the mean pCa50 was 5.93 ± 0.01 pCa units, which was significantly higher (P < 0.05) than that found in the type II fibres examined (5.83 ± 0.01 pCa units in 30 type II fibres, obtained from 10 of the same subjects). The Hill coefficient (h) of the fits was not significantly different between the type I fibres (5.2 ± 0.2) and the type II fibres (5.1 ± 0.2). The difference in the pCa50 is only small, but nevertheless will substantially affect the responses of the individual muscle fibres. This is most clearly seen in the force–[Ca2+] relationship examples shown in Fig. 1A. It is apparent that the force produced at pCa 6 (i.e. 1 μm free Ca2+) is >40% of maximum in the type I fibre but <20% of maximum in the type II fibre. As the cytoplasmic [Ca2+] is tightly controlled in this range by Ca2+ binding and release from troponin C and Ca2+ binding and uptake by the SERCA, the precise Ca2+ dependence of the contractile apparatus will be critical for force production and relaxation. The method of assaying the total amount of Ca2+ contained in a fibre has been described in detail previously (Fryer & Stephenson, 1996; Owen et al. 1997; Dutka et al. 2005) and is illustrated in Fig. 2. The given skinned fibre segment was briefly equilibrated in a solution containing a known concentration of BAPTA and then transferred into an emulsion of Triton X–100 and paraffin oil in order to lyse all intracellular membranous compartments and release any Ca2+, which then remained trapped within the fibre space. If an appropriate [BAPTA] was used, the BAPTA buffered the rise in free [Ca2+] sufficiently such that the fibre produced a detectable but non-maximal level of force. In such a situation the total amount of Ca2+ present within the fibre could be calculated from the [BAPTA] in the pre-equilibrating solution and the amplitude of the relative force response (see Methods). If zero or maximum force was produced upon lysis, the response indicated only an upper or a lower estimate of the total fibre Ca2+, respectively. Experiments were performed using fresh muscle fibres that had been skinned under paraffin oil, and hence the fibres initially still contained their normal endogenous Ca2+ content. Figure 2A presents the results for a typical type II fibre, which was equilibrated in 0.7 mm BAPTA and produced ∼40% of maximal force when lysed in TX–oil. Similar results were found in every endogenously loaded type II fibre examined from the young adult subjects, with a detectable, non-maximal force being elicited when the [BAPTA] was in the range 0.65–0.75 mm, and with maximal or zero force being elicited if the [BAPTA] was <0.6 mm or >0.8 mm, respectively (results not shown). The responses in type I fibres were very similar, except that the optimal [BAPTA] was slightly lower (∼0.60–0.70 mm). Such data indicated that the mean (±SEM) of the endogenous Ca2+ content was 0.76 ± 0.03 mmol per litre fibre volume in the type I fibres (n= 8) and slightly higher, 0.85 ± 0.02 mmol l−1, in the type II fibres (n= 15; P < 0.05). Further measurements were performed to ascertain the total Ca2+ content in skinned fibres (i) when the SR was loaded to its maximum capacity, by pre-exposing the fibre to the load solution for 4 min (e.g. Fig. 2B), and (ii) when the SR had been depleted of all readily releasable Ca2+ by a 1 min pre-exposure to the caffeine-low [Mg2+]-based 'full release solution' (e.g. Fig. 2C). Such experiments indicated that the mean (±SEM) of the maximal Ca2+ capacity was 1.44 ± 0.04 mmol l−1 in the type I fibres (n= 14) and 1.79 ± 0.03 mmol l−1 in the type II fibres (n= 19; P < 0.05). In the cases where the SR had been depleted prior to the BAPTA-lysing procedure, the mean total amount of Ca2+ remaining was determined to be 0.08 ± 0.01 mmol l−1 in type I fibres (n= 8) and <0.07 mm in type II fibres (n= 11). In the latter fibres, no force response was elicited upon fibre lysing even though there was only 0.025 mm BAPTA present, and consequently only an upper estimate of the Ca2+ content could be obtained. It was expected that the lysing of the SR in the TX–oil would have rendered the SERCA pumps in a non-functional state with relatively low affinity for Ca2+, hence preventing them from contributing to the total number of high affinity Ca2+ binding sites present in the fibre (those primarily being BAPTA and TnC). In order to verify that the low force responses seen in the depleted SR experiments were not due to the SERCA binding appreciable amounts of Ca2+, a further three type I and seven type II fibres from three subjects were examined with 50 μm TBQ present in both the BAPTA pre-equilibration solution and the full release solution (see Methods). TBQ drives SERCA into a state with low Ca2+ affinity (Wictome et al. 1992), but its presence did not cause any appreciable d